Synthesis and characterization of magnetic polyHIPEs with humic acid surface modified magnetic iron oxide nanoparticles - Mert, Emine Hilal; Yildirim, Huseyin; Uzumcu, Ahmet Talha; Kavas, Huseyin (ELSEVIER, 2013)
Magnetic macroporous polymer monoliths have been prepared using styrene/divinylbenzene (S/DVB) high internal phase emulsions (HIPEs) as templates. Humic acid surface modified iron oxide magnetic nanoparticles (Fe3O4@HA) have been used to prepare magnetic emulsion templates. The effect of magnetic particle concentration has been investigated by changing the ratio of Fe3O4@HA nanoparticles in the continuous phase. Highly macroporous polymers with magnetic response were obtained by the removal of the internal phase after the curing of emulsions at 80 degrees C. Fe3O4@HA particles were characterized by XRD and FTIR. The porosity, pore morphology and magnetic properties of the macroporous polymers were characterized as a function of the Fe3O4@HA concentration by scanning electron microscopy (SEM), Brunauer-Emmet-Teller (BET) molecular adsorption method and vibrating sample magnetometry (VSM), respectively. BET and VSM measurements demonstrated that the specific surface area and the saturation magnetization of the polymer monoliths were changed according to the Fe3O4@HA concentration between 8.77-35.08 m(2) g(-1) and 0.63-11.79 emu g(-1), respectively. Resulting magnetic monoliths were tested on the adsorption of Hg(II) and atomic absorption spectroscopy (AAS) was used to calculate the adsorption capacities. The maximum adsorption capacity of the magnetic monoliths was calculated to be 20.44 mmol g(-1) at pH 4. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Magnetic polymers; Macroporous polymers; HIPE; Humic acid; Fe3O4@HA; HIGHLY CONCENTRATED EMULSIONS; INTERNAL PHASE EMULSIONS; UBER DIE POLYMERISATION; HEAVY-METALS; SUSPENSION POLYMERIZATION; NANOCOMPOSITE MATERIALS; DIMETHACRYLATE) BEADS; REMOVAL; MICROSPHERES; MONOLITHS; Chemistry; Engineering; Polymer Science